The Effect of Interactive Learning Media on Elementary School Students' Reading and Viewing Abilities: Pengaruh Media Pembelajaran Interaktif Terhadap Kemampuan Membaca dan Memirsa Siswa Sekolah Dasar - Purnomo, Aris Widi Purnomo; Nisa, Ana Fitrotun; Masjid, Akbar Al; Djufri, Elyas (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Multimodal literacy is essential for elementary students in technology-rich learning environments. Specific Background Reading and viewing abilities remain limited when classroom learning relies on conventional media that are less interactive and less connected to students’ cultural context. Knowledge Gap Previous studies have mostly examined digital learning media for general cognitive outcomes, while research on reading and viewing abilities through interactive media integrated with local values remains limited. Aims This study analyzed the use of interactive learning media integrated with local values for elementary students’ reading and viewing abilities. Results The experimental class increased from a pretest mean score of 63.50 to a posttest mean score of 81.50, while the control class increased from 63.00 to 70.25. The experimental class recorded a 28.30% increase, compared with 11.50% in the control class. The independent t-test showed a significant difference between groups, with t = 4.62 and p = 0.000 < 0.05. Novelty The study combines interactive learning media with local values in reading and viewing learning. Implications The findings provide practical guidance for teachers in designing meaningful, technology-based, and culturally relevant literacy learning. Highlights • The treatment class reached a posttest mean score of 81.50.• Statistical testing showed t = 4.62 and p = 0.000.• Learning activities involved video, animation, narration, quizzes, and evaluation tasks. Keywords Interactive Learning Media; Reading And Viewing; Multimodal Literacy; Local Values; Elementary Students